2017
DOI: 10.1111/mms.12451
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for identifying individual cetaceans using facial features and symmetry: A test case using dolphins

Abstract: Individual identification plays a major role in our understanding of the biology, ecology and behavior in cetaceans. Being able to tell individuals apart can provide invaluable insight into basic biological and scientific questions, but is also highly relevant to science‐based conservation. Given the importance of individual identification, it appears vital to improve existing identification methods and find new ones. Here, we present a novel identification method of using facial information, with common bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…When coupled with information on behaviour and interactions with human activities, it is a powerful tool in the study and conservation of social animals. Common bottlenose dolphins ( T. truncatus ) inhabit the Gulf of Trieste and adjacent areas of northern Adriatic Sea, where they have been studied since 2002 (Genov et al 2008 , 2017 ). Here, we examine the social structure of local dolphins and assess whether different population segments show differences in behaviour and interactions with human activities.…”
Section: Introductionmentioning
confidence: 99%
“…When coupled with information on behaviour and interactions with human activities, it is a powerful tool in the study and conservation of social animals. Common bottlenose dolphins ( T. truncatus ) inhabit the Gulf of Trieste and adjacent areas of northern Adriatic Sea, where they have been studied since 2002 (Genov et al 2008 , 2017 ). Here, we examine the social structure of local dolphins and assess whether different population segments show differences in behaviour and interactions with human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is no easy solution to this problem, which is a limitation of all demographic analyses of cetacean populations. Some alternative to natural marks has recently emerged based on facial recognition of dolphins (Genov, Centrih, Wright, & Wu, ) and should be considered for identifying young animals in the future allowing for a more direct approach to estimate young survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The dolphin stayed with the ship, and detailed photographs could be made. Comparison of the dorsal fin and facial features (Genov et al, 2018) with images of known individuals from the French coast showed that this individual is known as 'Zafar' (Figure 3, Supplementary Figure S2), a male solitary-sociable dolphin that shows atypical behaviour in seeking out human company (Nunny & Simmonds, 2019). This individual might have been observed as early as 2002, but the first confirmed sighting dates back to 2017, when he was seen off Lomener, Brittany, France (Zafar le dauphin blogspot, 2018).…”
Section: Solitary Bottlenose Dolphin In Amsterdammentioning
confidence: 99%